Purification of infective bluetongue virus particles by immuno-affinity chromatography using anti-core antibody - Chand, Karam (Virusdisease, 2016)
An immuno-affinity chromatography technique for purification of infective bluetongue virus (BTV) has been descried using anti-core antibodies. BTV anti-core antibodies (prepared in guinea pig) were mixed with cell culture-grown BTV-1 and then the mixture was added to the cyanogens bromide-activated protein-A Sepharose column. Protein A binds to the antibody which in turn binds to the antigen (i.e. BTV). After thorough washing, antigen–antibody and antibody-protein A couplings were dissociated with 4M MgCl(2), pH6.5. Antibody molecules were removed by dialysis and virus particles were concentrated by spin column ultrafiltration. Dialyzed and concentrated material was tested positive for BTV antigen by a sandwich ELISA and the infectivity of the chromatography-purified virus was demonstrated in cell culture. This method was applied for selective capture of BTV from a mixture of other viruses. As group-specific antibodies (against BTV core) were used to capture the virus, it is expected that virus of all BTV serotypes could be purified by this method. This method will be helpful for selective capture and enrichment of BTV from concurrently infected blood or tissue samples for efficient isolation in cell culture. Further, this method can be used for small scale purification of BTV avoiding ultracentrifugation.